, DMCN 43: 234–8 (Developmental Medicine and Child Neurology, 2001)
AIM: To develop the Pediatric Autoimmune encephalitis Severity Scale (PASS) using expert consensus and the Delphi process, and validate it in children with autoimmune encephalitis. METHOD: This prospective observational study enrolled children who underwent serial rating with PASS, the Clinical Assessment Scale in Autoimmune Encephalitis (CASE), and the modified Rankin Scale, at eight time points until 6 months of presentation. Clinical outcomes included the Pediatric Quality of Life Inventory (PedsQL) score (parent-rated) and developmental and intellectual outcome at 6 months. Interrater agreement, internal consistency, and correlations of PASS and CASE with clinical outcomes were compared. RESULTS: There were 361 assessments in 27 children (11 females, 16 males) with autoimmune encephalitis (15 with antibody-negative autoimmune encephalitis, 11 with N-methyl-D-aspartate receptor antibody encephalitis, and one with steroid-responsive encephalopathy associated with autoimmune thyroiditis) with a median age at onset of 4 years (interquartile range = 3 years to 6 years 5 months). There was excellent interrater agreement for PASS and CASE with comparable intraclass correlation coefficients (0.984 vs 0.983). The worst PASS score was inversely correlated with the final PedsQL score (r = -0.42, p = 0.047). Factor analysis revealed distinct 'cognitive and behavioural' and 'disinhibition and excitability' dimensions in the PASS items. INTERPRETATION: PASS is a severity assessment tool for autoimmune encephalitis in children and offers an alternative to adult scales, which may be difficult to use in children.